miR-205 Expression Elevated With EDS Treatment and Induced Leydig Cell Apoptosis by Targeting RAP2B via the PI3K/AKT Signaling Pathway - Cui, Yang; Chen, Rui; Ma, Lin; Yang, Wenjing; Chen, Mingyue; Zhang, Yanghai; Yu, Shuai; Dong, Wuzi; Zeng, Wenxian; Lan, Xianyong; Pan, Chuanying (Frontiers in Cell and Developmental Biology, 2020)
The adult Leydig cells (ALCs), originated from stem Leydig cells (SLCs), can secrete testosterone which is essential for germ cell development and sexual behavior maintenance. As a synthetic compound, ethane dimethane sulphonate (EDS), a well-known alkylating agent, has been reported to specifically ablate ALCs. In this study, EDS was verified to ablate differentiated pig LCs by experiments. Subsequently, the primary isolated pig LCs (containing SLCs and differentiated LCs) and EDS-treated LCs (almost exclusively SLCs) were collected for RNA-seq. 4,904 genes and 15 miRNAs were differently expressed between the two groups. Down-regulated genes in the EDS-treated group were mainly related to steroid hormone biosynthesis. The highest up-regulation miRNAs was miR-205 after EDS treatment. Additionally, miR-205 was expressed more highly in pig SLCs clones compared with differentiated LCs. Through qRT-PCR, western blot (WB), TUNEL, EDU and flow cytometry, miR-205 was found to induce cell apoptosis, but did not affect proliferation or differentiation in both TM3 and GC-1spg mouse cell lines. Through luciferase reporter assays and WB, RAP2B was identified as a target gene of miR-205. Besides, overexpression of miR-205 inhibited the expressions of PI3K, Akt and p-AKT. All these findings were helpful for elucidating the regulation mechanism in pig LCs.